2016
DOI: 10.1002/bit.25964
|View full text |Cite
|
Sign up to set email alerts
|

Decellularisation and histological characterisation of porcine peripheral nerves

Abstract: Peripheral nerve injuries affect a large proportion of the global population, often causing significant morbidity and loss of function. Current treatment strategies include the use of implantable nerve guide conduits (NGC's) to direct regenerating axons between the proximal and distal ends of the nerve gap. However, NGC's are limited in their effectiveness at promoting regeneration Current NGCs are not suitable as substrates for supporting either neuronal or Schwann cell growth, as they lack an architecture si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 65 publications
2
36
0
Order By: Relevance
“…Related to fresh healthy nerves, the values of Young Modulus in mice and rats are very low [63] when compared to pigs [64] creating a range that goes from 0.5 MPa (in mice) to 7.75 MPa (in pigs). In this respect, comparing our data with the values of mechanical properties to fresh healthy in vivo nerves in pigs [64,65] the values were similar and in the same range of the ones reported in the literature for porcine peroneal and tibial nerves (≈ 7.43-7.75 MPa).…”
Section: Discussionsupporting
confidence: 88%
“…Related to fresh healthy nerves, the values of Young Modulus in mice and rats are very low [63] when compared to pigs [64] creating a range that goes from 0.5 MPa (in mice) to 7.75 MPa (in pigs). In this respect, comparing our data with the values of mechanical properties to fresh healthy in vivo nerves in pigs [64,65] the values were similar and in the same range of the ones reported in the literature for porcine peroneal and tibial nerves (≈ 7.43-7.75 MPa).…”
Section: Discussionsupporting
confidence: 88%
“…The basic problem with allogenic nerve development is that a standard evaluation protocol for the decellularized nerve has not been established (Philips, Cornelissen, & Carriel, ). A comprehensive approach including various evaluation tools was recently emphasized for verification of the decellularized tissue or organs (Zilic, Wilshaw, & Haycock, ). Crapo et al () suggested a criteria for evaluation of cell removal composed of histological analysis with H&E or DAPI staining and DNA quantification.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that the nerve defects can be repaired by acellular nerve allografts to some degree (Saheb‐Al‐Zamani et al, ; Tajdaran, Gordon, Wood, Shoichet, & Borschel, ). The acellular nerve grafts of different mammalian species that are chemically extracted possess favorable biocompatibility, thus the utilization of heterogenetic acellular nerves seems to be capable of augmenting the insufficient source of nerve grafts in clinical practice (Zhang, Tong et al, ; Zilic, Wilshaw, & Haycock, ). However, there are few reports about nerve repairs by ANX.…”
Section: Discussionmentioning
confidence: 99%